Proton MRS of cervical cancer at 7 T - Arteaga de Castro, C.S.; Hoogendam, J.P.; Kalleveen, I.M.L.; Raaijmakers, A.J.E.; Zweemer, R.P.; Verheijen, R.H.M.; Luijten, P.R.; Veldhuis, W.B.; Klomp, D.W.J. (NMR in biomedicine, 2019)
The differentiation grade of cervical cancer is histologically assessed by examining biopsies or surgical specimens. MRS is a highly sensitive technique that images tissue metabolism and can be used to increase the specificity of tissue characterization in a non‐invasive manner. We aim to explore the feasibility of using in vivo 1H‐MRS at 7 T in women with cervical cancer to study tissue fatty acid composition. 10 women with histologically proven Stage IB1‐IIB cervical cancer were scanned with a whole‐body 7 T MR system with a multi‐transmit system and an internal receive only monopole antenna. A STEAM sequence was used to obtain 1H‐MRS data. Fatty acid resonances were fitted with Lorentzian curves and the 2.1 ppm/1.3 ppm ratios were calculated. 1H‐MRS data showed fatty acid signals resonating at 2.1 ppm, 1.9 ppm, 1.5 ppm, 1.3 ppm and 0.9 ppm. Mean 2.1/1.3 ppm ratios were 0.019 ± 0.01, 0.021 ± 0.006, 0.12 ± 0.089 and 0.39 ± 0.27 for normal, Grade I, Grade II and Grade III groups respectively. Poorly differentiated tumor tissue (Grade III) showed elevated fatty acid ratios when compared with the well differentiated tumor (Grade I) or normal tissue. 1H‐MRS in cervical cancer at 7 T is feasible and individual fatty acid signals were detected. In addition, poorly differentiated tumors show more fatty acid unsaturation. The 2.1 ppm/1.3 ppm ratio has potential for tumor characterization in a non‐invasive manner for uterine cervical cancer. The feasibility of fatty acid characterization was investigated at ultra‐high field. Fatty acids in uterine cervix were measured in a single voxel with MRS at 7 T in 10 patients with cervical cancer and 5 healthy volunteers. Fatty acids were fitted and the 2.1 ppm/1.3 ppm ratios were calculated for each subject. These showed a trend towards unsaturation of the fatty acids in poorly differentiated tumors, when compared with well differentiated tumors or normal tissue.